1999
DOI: 10.1177/019874299902400204
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from the Inclusion of Students with Emotional and Behavioral Disorders in One Junior High School

Abstract: The purpose of this qualitative study was to ascertain what effects an inclusive setting had on 14 students with emotional and behavioral disorders (E/BD) in terms of school and academic behavior, social skills, and acceptance by peers according to teachers, administrators, general education peers, and the students themselves. The researchers focused on five main themes: (1) overall perception of the program, (2) curriculum adaptation, (3) effect on student social and personal behavior, (4) administrative supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Farlow (1996), O'Neil (1994), Mastropieri and Scruggs (2000), and Salend (2001) emphasized the importance of students learning to accept diversity among fellow students and community members. Other supportive points include the importance of appropriate role models (Farlow, 1996;Friend & Bursuck, 1999;Mastropieri & Scruggs, 2000;Oberti, 1993;Salend, 2001), appropriate preparation for future community living (Farlow, 1996;O'Neil, 1995), establishment of a network of community supports (Farlow, 1996;Farmer & Farmer, 1996;O'Neil, 1995), higher teacher expectations for mainstream behaviors and skills (Friend & Bursuck, 1999;Oberti, 1993), and greater social gains for students with disabilities (D'Alonzo, Giordano, & Vanleeuwen, 1997;Gibb, Allred, Ingram, Young, & Egan, 1999;Hendrickson, Shokoohi-Yekta, Hamre-Nietupski, & Gable, 1996).…”
mentioning
confidence: 99%
“…Farlow (1996), O'Neil (1994), Mastropieri and Scruggs (2000), and Salend (2001) emphasized the importance of students learning to accept diversity among fellow students and community members. Other supportive points include the importance of appropriate role models (Farlow, 1996;Friend & Bursuck, 1999;Mastropieri & Scruggs, 2000;Oberti, 1993;Salend, 2001), appropriate preparation for future community living (Farlow, 1996;O'Neil, 1995), establishment of a network of community supports (Farlow, 1996;Farmer & Farmer, 1996;O'Neil, 1995), higher teacher expectations for mainstream behaviors and skills (Friend & Bursuck, 1999;Oberti, 1993), and greater social gains for students with disabilities (D'Alonzo, Giordano, & Vanleeuwen, 1997;Gibb, Allred, Ingram, Young, & Egan, 1999;Hendrickson, Shokoohi-Yekta, Hamre-Nietupski, & Gable, 1996).…”
mentioning
confidence: 99%
“…(Gibb, Allred, Ingram, Young & Egan, 1999, Castle & Parsons, 1997. In both countries there is however a continued belief that such students can and should be given every opportunity to remain within the least restrictive setting possible and that all school districts or LEA'S should be working towards inclusion or integration (U.S. Department of Education, 1994;The Green Paper, DFEE, 1997;SEN Action Plan, DFEE, 1998a;Social Inclusion: Student Support, DFEE, 1999).…”
Section: V) a Rigorous Approach For The Student With Emotional And Bementioning
confidence: 99%
“…In both countries there is however a continued belief that such students can and should be given every opportunity to remain within the least restrictive setting possible and that all school districts or LEA'S should be working towards inclusion or integration (U.S. Department of Education, 1994;The Green Paper, DFEE, 1997;SEN Action Plan, DFEE, 1998a;Social Inclusion: Student Support, DFEE, 1999). In the USA such inclusion does appear to be increasing for students with certain disorders or disabilities but those displaying emotional or behavioural problems still fail with regularity in general education classrooms and currently continue to be educated in the most restrictive environments (Gibb et al, 1999). The CDE initiatives outlined in this paper should provide welcome ideas for those attempting to increase the success of inclusion for children with EBD in mainstream classrooms both in the USA and the UK, (TES, 1999), and should help to counteract the arguments of those who question the ability of such students to ever successfully integrate (Webber, 1993).…”
Section: V) a Rigorous Approach For The Student With Emotional And Bementioning
confidence: 99%
“…Although the results are mixed, some studies have demonstrated that with appropriate support and adaptations, students with disabilities may perform as well, if not better, in general education (Gibbs, Alfred, & Ingram, 1999;Rea, McLaughlin, & WaltherThomas, 2002). General education teachers may hold students to higher standards for performance and behavior.…”
mentioning
confidence: 99%